Впровадження засобів цифровізації у професійну підготовку фахівців - Кучай Тетяна; Kuchai Tatiana; Kucsáj Tetjána; Кучай Олександр; Kuchai Oleksandr; Kucsáj Olekszandr; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2025)
Резюме. Глобальна цифровізація формує новий тип культури сучасного суспільства – цифрову культуру, що перш за все потребує модернізації та розвитку системи професійної освіти у контексті готовності адекватного використання можливостей технологічних новацій та формування сучасних професійно значущих якостей майбутніх фахівців. Цифровізація освіти поширюється на весь процес підготовки майбутніх фахівців, починаючи з визначення змісту і до контролю щодо якості освоєння освітньої програми Цифровізація у закладах вищої освіти змінює роль викладача, який вже не передає, транслює знання студентам, а стає проєктувальником освітнього процесу.

Abstract. Global digitalization is forming a new type of culture of modern society - digital culture, which primarily requires modernization and development of the professional education system in the context of readiness for adequate use of the opportunities of technological innovations and the formation of modern professionally significant qualities of future specialists. Digitalization of education extends to the entire process of training future specialists, starting from determining the content and ending with control over the quality of mastering the educational program. Digitalization in higher education institutions changes the role of the teacher, who no longer transfers, broadcasts knowledge to students, but becomes a designer of the educational process. Modern digital technologies make it possible to create a personal learning environment that combines the capabilities of formal and informal education. The use of digital technologies in the process of training future specialists increases their professional capabilities, because the future specialist masters professional knowledge, skills, abilities and experience, which together enable the free use of digital technologies. Also, the digitalization of professional training involves the formation of a digital culture in future specialists, which allows for the optimal use of digital tools, new technologies, and the development of professionally important competencies. Educational technologies should ensure the involvement of applicants and the responsibility of educational institutions for participation in global knowledge networks. Smart pedagogy should stimulate this participation, ensuring the systematic introduction of interactive social dynamics into educational transmedia spaces. The priority tasks of the educational process in the context of the implementation of digital transformation with the use of intelligent information technologies are highlighted.
Implementation of digitalization means in the professional training of specialists
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: цифровізація; академічна доброчесність; професійна підготовка фахівців; штучний інтелект; цифрова культура; технологічні новації